Diversity, distribution and taxonomy of the Australian agathidine genera Camptothlipsis Enderlein, Lytopylus Foerster and Therophilus Wesmael (Hymenoptera: Braconidae: Agathidinae) - Stevens, Nicholas B.; Austin, Andrew D.; Jennings, John T. (Zootaxa, 2011)
The braconid subfamily Agathidinae is a large group of koinobiont endoparasitic wasps of lepidopteran larvae. Until recently, three of the 10 agathidine genera that occur in Australia, Camptothlipsis Enderlein, Lytopylus Foerster and Therophilus Wesmael, were treated as synonyms of Bassus F. s.l. Of these three genera, Therophilus is the most speciose and widely distributed in Australia, and is one of only two agathidine genera whose members are associated with a putative mimicry complex of braconid wasps and other insects comprising species that have a distinctive black, red-orange and white colour pattern. Australian species, previously considered under Bassus s.l., have received little attention since their original description nearly 90 years ago and, not surprisingly, this earlier work is insufficient for reliable species identification. The present study updates the taxonomy of the described species, presents a more thorough assessment of intraspecific variation, and provides a key for species of Therophilus. Four new species are described that support morphological and molecular phylogenetic studies on the Australian fauna: Camptothlipsis oliveri Stevens n. sp., representing the first described species for this genus in Australia, and Therophilus aalvikorum Stevens n. sp., T. mishae Stevens n. sp., and T. stephensae Stevens n. sp., whose descriptions also extend the morphological limits of Therophilus in Australia. In addition, the introduced Lytopylus rufipes (Nees von Esenbeck) is redescribed, this species representing the only member of the genus known from Australia. Significantly, two species of Therophilus, T. unimaculatus (Turner) and T. rugosus (Turner), are important parasitoids of the native Australian lepidopterans Etiella behrii Zeller (Pyralidae) and Epiphyas postvittana (Walker) (Tortricidae) that have become significant pests in southern and eastern Australia, as well as in several other countries.